An improved latent heat thermal energy storage using two layers of metal foams - Ghalambaz, Mohammad; Fteiti, Mehdi A.; Younis, Obai; Sheremet, Mikhail A.; Hasan, Hiba A. (Applied thermal engineering)
Latent Heat Thermal Energy Storage (LHTES) systems are essential due to their remarkable ability to compactly store significant thermal energy. Their pivotal role extends to various energy applications, prominently including solar heaters and waste thermal energy recovery initiatives. Metal foams have the ability to improve heat transmission and thermal charging of energy storage units dramatically. However, the metal foam cannot store latent heat energy, so the goal is to improve heat transfer by using minimal foam mass. Here, the LHTES is made of several parallel channel enclosures with a square cross-section of 120 mm in height/width. There is a 21 °C temperature difference between the heated channel walls and PCM fusion temperature. In the current study, the influence of the configuration of two metal foam layers was addressed on melting time in LHTES. The idea is to use heavy foam (porosity 0.90) in places where there is low convection and light foams (porosity 0.975) in places with good convection heat transfer to enhance thermal charging and keep the storage weight low. Therefore, three configurations of splitting into half, an L shape division, and splitting diagonally for foam layers were examined. The influence of metal foam configurations on melting volume fraction, thermal energy storage, isotherms, and streamlines was examined. The geometrical configuration of foam layers could significantly influence the thermal charging time and energy storage profiles. The best layer configuration was a horizontal splitting of the enclosure with a light foam layer (high porosity metal foam) at the top. The well-configured foam layer could complete the charging process in 837 s, 32% faster than the same splitting but placing the light foam layer at the bottom.